X² + 1 = 0
=> (x+1)² - 2x = 0
=> x+1 = √(2x)
or x - √(2x) + 1 = 0
Now take y=√x
So, the equation changes to
y² - y√2 + 1 = 0
By quadratic formula, we get:-
y = [√2 ± √(2–4)]/2
or √x = (√2 ± i√2)/2 or (1 ± i)/√2 [by cancelling the √2 in numerator and denominator and ‘i' is a imaginary number with value √(-1)]
or x = [(1 ± i)²]/2
So roots are [(1+i)²]/2 and [(1 - i)²]/2
Thus we got two roots but in complex plane. If you put this values in the formula for formation of quadratic equation, that is x²+(a+b)x - ab where a and b are roots of the equation, you will get the equation
x² + 1 = 0 back again
So it’s x=1 or x=-1
Answer:
1.)
2.)
Step-by-step explanation:
1.)
2.)
7 I just took the test! Hope this helped
3 4/10 is my answer
please can i have a brainliest
ΔTXV is an <span>isosceles triangle because ∡T = ∡X therefore TV = VX.
3x - 24 = 2x + 1 |subtract 2x from both sides
x - 24 = 1 |add 24 to both sides
x = 25
</span>